Endorphin Massage Reduces Back Pain Intensity in Third-Trimester Pregnant Women at Rismana Pakpahan’s Practice - Rijsubo, Primawaty Dwi; Pakpahan, Elfrida; Oktaviani, Emma; Aldriana, Nana; Wulandari, Sri; Wahyuny, Romy; Ginting, Johannes Bastira (Jurnal Keperawatan Priority, 2024)
The management of back pain in pregnant women using endorphin massage is an urgent need. This method not only helps reduce physical pain but also provides significant emotional and psychological benefits. Endorphin massage therapy can be an effective solution to improve the quality of life of pregnant women during pregnancy. This study aims to determine endorphin massage's effect on reducing back pain intensity in third-trimester pregnant women. This research is pre-experimental with a one-group pre-test and post-test approach, conducted at Puskesmas Rismana Pakpahan Ujungbatu in 2024. The population in this study consisted of 100 pregnant women, and the sample was taken using a purposive sampling technique with the criteria of third-trimester pregnant women experiencing back pain, willing to be respondents, and not having pregnancy complications. Based on these criteria, 30 pregnant women were obtained as samples. The statistical test was bivariate with a t-dependent test at 95% significance level. The results showed a significant difference in the average back pain intensity scale before (pre-test) and after (post-test) endorphin massage, with an average decrease of 4.667. The statistical test results showed a p-value of 0.0001, more diminutive than 0.05, indicating a significant relationship between the variables studied. This study concludes that there is a substantial change in the intensity of back pain in pregnant women after being given endorphin massage treatment. These results indicate that endorphin massage therapy is effective in reducing back pain and can be used as a safe and beneficial treatment method for pregnant women.